2021
DOI: 10.1088/1748-9326/ac40b1
|View full text |Cite
|
Sign up to set email alerts
|

A gridded inventory of Canada’s anthropogenic methane emissions

Abstract: Canada's anthropogenic methane emissions are reported annually to the United Nations Framework Convention on Climate Change (UNFCCC) through Canada's National Inventory Report (NIR). Evaluation of this policy-relevant inventory using observations of atmospheric methane requires prior information on the spatial distribution of emissions but that information is lacking in the NIR. Here we spatially allocate the NIR methane emissions for 2018 on a 0.1º x 0.1º grid (≈ 10 km x 10 km) for individual source sectors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…None of the three reported substances used for this study (e.g., sulfur dioxide, carbon monoxide, and nitrogen dioxide) are reported under the Canadian Greenhouse Gas Reporting Program (GHGRP) [26]. Therefore, this study only focused on the limitations of the NPRI tool.…”
Section: Methodsmentioning
confidence: 99%
“…None of the three reported substances used for this study (e.g., sulfur dioxide, carbon monoxide, and nitrogen dioxide) are reported under the Canadian Greenhouse Gas Reporting Program (GHGRP) [26]. Therefore, this study only focused on the limitations of the NPRI tool.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 1b shows the bottom-up O/G methane emissions from the US and Canada in 2018 based on the gridded versions of the EPA and ECCC national inventories (Maasakkers et al, 2016;Scarpelli et al, 2021), which are used as prior estimates in our inversion framework.…”
Section: Inversion Ensemble and Uncertainty Analysismentioning
confidence: 99%
“…We conduct inversions of TROPOMI observations for 22 months (May 2018 -February 2020) in the five rectangular domains of Fig. 1a, which encompass over 98% of total O/G emissions, 97% of oil production and 99% of gas production in the continental US and Canada (Enverus DrillingInfo, 2020; Maasakkers et al, 2016;Scarpelli et al, 2021), and include all 19 major O/G production basins shown in Fig. 1b (see Fig.…”
Section: Inversion Ensemble and Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We use the anthropogenic emissions inventory for the US from Maasakkers et al (2016) for 2012, and the O/G emissions are updated to the year 2018 based on activity data in the Enverus DrillingInfo database (Enverus DrillingInfo, 2020). For Canada, we use anthropogenic emissions from Scarpelli et al ( 2021) based on the Environment and Climate Change Canada's (ECCC) inventory for 2018 (ECCC, 2020). The optimal value of g can be selected when…”
mentioning
confidence: 99%